Information systems and technology for organizations in a networked society - Issa, Tomayess; Isaias, Pedro; Kommers, P. (Idea Group, U.S, 2013)
Modern society is increasingly information-driven, relying heavily on Information Systems (IS) and Information Technology (IT). Business enterprises are no exception, and managers and leaders must learn to make the most of the information resources at their disposal or risk falling behind the times. Information Systems and Technology for Organizations in a Networked Society discusses methods of using information technologies to support organizational and business objectives in both national and international contexts. This reference book describes the latest research on both the technical and non-technical aspects of contemporary information societies, including e-commerce, e-learning, e-government, and e-health; supporting professionals and academicians in developing a deeper understanding of the most effective models for communication, collaboration, and business development. This book is part of the Advances in Business Information Systems and Analytics series collection.